Peranan Motivasi dalam Memediasi Hubungan Pengawasan dan Kinerja Ojek Online Muslim di Kota Bekasi - Rycha Kuwara Sari; Muhammad Richo Rianto; Adi Wibowo Noor Fikri; Kardinah Indrianna meutia (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aims to measure the role of motivation as a mediator in the relationship between supervision and performance. This research is a quantitative research that uses the independent variable of supervision, the dependent variable of performance and the variable of motivational as mediator. This research was conducted on Muslim online motorcycle taxi drivers in the city of Bekasi. The sample in this study used random sampling method which was conducted on 130 Muslim online motorcycle taxi drivers in the city of Bekasi. Smartpls 3.3.3 is a statistical analysis tool in this study by using the outer test and the inner model test to test the feasibility of the data and answer the hypothesis. The results of this study found that direct supervision had no effect on performance, while supervision had an effect on motivation and motivation had an effect on performance. The most important research result is that motivation can be a mediator in the relationship between supervision and performance of online motorcycle taxi drivers in the city of Bekasi. This study focuses on the role of motivation as a mediation. This study also raises a new phenomenon, namely the performance of Muslim online motorcycle taxi drivers conducted in the city of Bekasi, which is one of the provinces with the largest Muslim population.